The Effectiveness of a Behavioral-Cognitive Counseling Program in Reducing Symptoms of Social Anxiety and Improving Self-Esteem among Adolescent Female Students in Karak, Jordan - Tahani Al-Shobaki (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the effectiveness of a behavioral cognitive counseling program in reducing symptoms of social anxiety and improving self-esteem among a sample of adolescent female students in Karak Governorate. The study sample consisted of (42) high school students who obtained high scores on the social anxiety scale, To achieve the goals of the study, the researcher used a social anxiety scale as a measure of self-esteem and a counseling program. The members of the study sample were randomly distributed into two groups: an experimental group (n=20) that participated in a counseling program and a control group (n=22) that received no training. The performance of the experimental and control groups was measured on the social anxiety and the self-esteem scales before and after the counseling program. The results of the study showed that there were statistically significant differences between the experimental and control groups in social anxiety and self-esteem in favor of the experimental group. The study recommends the adoption of cognitive-behavioral therapy as an effective treatment to reduce the symptoms of social anxiety disorder and to improve self-esteem.